Good practices for dialysis education, treatment, and eHealth: A scoping review. - Anita van Eck van der Sluijs; Sanne Vonk; Brigit C van Jaarsveld; Anna A Bonenkamp; Alferso C Abrahams (PLoS ONE)
Background Recommendations regarding dialysis education and treatment are provided in various (inter)national guidelines, which should ensure that these are applied uniformly in nephrology and dialysis centers. However, there is much practice variation which could be explained by good practices: practices developed by local health care professionals, which are not evidence-based. Because an overview of good practices is lacking, we performed a scoping review to identify and summarize the available good practices for dialysis education, treatment, and eHealth. Methods Embase, Pubmed, the Cochrane Library, CINAHL databases and Web of Science were searched for relevant articles using all synonyms for the words 'kidney failure', 'dialysis', and 'good practice'. Relevant articles were structured according to the categories dialysis education, dialysis treatment or eHealth, and assessed for content and results. Results Nineteen articles (12 for dialysis education, 3 for dialysis treatment, 4 for eHealth) are identified. The good practices for education endorse the importance of providing complete and objective predialysis education, assisting peritoneal dialysis (PD) patients in adequately performing PD, educating hemodialysis (HD) patients on self-management, and talking with dialysis patients about their prognosis. The good practices for dialysis treatment focus mainly on dialysis access devices and general quality improvement of dialysis care. Finally, eHealth is useful for HD and PD and affects both quality of care and health-related quality of life. Conclusion Our scoping review identifies 19 articles describing good practices and their results for dialysis education, dialysis treatment, and eHealth. These good practices could be valuable in addition to guidelines for increasing shared-decision making in predialysis education, using patients' contribution in the implementation of their dialysis treatment, and advanced care planning.